Kinetics modelling of green solvents delignified oil palm empty fruit bunch pyrolysis via thermogravimetric analysis - Yiin, Chung Loong; Andrian Zi, En Ku; Bridgid Chin, Lai Fui; Serene Lock, Sow Mun; Armando Tibigin, Quitain (AIP Publishing, 2025)
The urge to seek for green alternatives in replacement of conventional pretreatment methods has led to the disclosure of a new class of designer solvents termed Low-Transition-Temperature-Mixtures (LTTMs) as a prospective green pretreatment method. Correspondingly, a kinetic study on the pyrolysis process of sucrose-based LTTMs pretreated oil palm empty fruit bunch (EFB) was carried out by using thermogravimetric analysis (TGA) equipment at various heating rates of 10, 30, 50 and 70 ℃/min. The present research project focused on the thermal degradation and determination of kinetic parameters such as the activation energy and frequency factor by means of three model-free methods namely Kissinger model, Kissinger-Akahira-Sunose (KAS) model and Flynn-Wall-Ozawa (FWO) model. The results derived from TGA showed that three stages of thermal decomposition of oil palm EFB were identified such as dehydration, devolatilisation and degradation. In addition, the weight loss curves indicated that the pyrolysis of untreated and delignified EFB took place mainly in the range of 200 ℃ to 400 ℃. Moreover, the peaks of the differential thermogravimetry (DTG) curves which represent maximum degradation tended to shift slightly towards the right at higher temperature when the heating rates were being increased. The results showed that the values of kinetic parameters evaluated from model-free methods were compatible with each other whether it be untreated EFB or the delignified EFB. Furthermore, there was an increase in the activation energies after the process of pretreatment. Specifically, the activation energies increased from 129.40 kJ/mol to 188.83 kJ/mol for Kissinger model; 167.87 kJ/mol to 194.93 kJ/mol for KAS model; 167.22 kJ/mol to 190.09 kJ/mol for FWO model.